Lethal agent : a Mitch Rapp novel - Mills, Kyle, 1966-; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2019)
An unprecedented and terrifying bioterrorism plot threatens to kill millions in the midst of a divisive presidential election in this new thriller from the #1 New York Times bestselling Mitch Rapp series. A toxic presidential election is underway in an America already badly weakened by internal divisions. While politicians focus entirely on maintaining their own power and privilege, ISIS kidnaps a brilliant French microbiologist and forces him to begin manufacturing anthrax. Slickly produced videos chronicling his progress and threatening an imminent attack are posted to the Internet, intensifying the hysteria gripping the US. ISIS recruits a Mexican drug cartel to smuggle the bioweapon across the border, but it's really just a diversion. The terrorist organization needs to keep Mitch Rapp and Irene Kennedy distracted long enough to weaponize a deadly virus that they stumbled upon in Yemen. If they succeed, they'll trigger a pandemic that could rewrite the world order. Rapp embarks on a mission to infiltrate the Mexican cartels and track down the ISIS leader who he failed to kill during their last confrontation. But with Washington?s political elite increasingly lined up against him, he knows he'll be on his own.